2019
DOI: 10.1136/bmjopen-2019-033137
|View full text |Cite
|
Sign up to set email alerts
|

The social cure of social prescribing: a mixed-methods study on the benefits of social connectedness on quality and effectiveness of care provision

Abstract: ObjectivesThis study aimed to assess the degree to which the ‘social cure’ model of psychosocial health captures the understandings and experiences of healthcare staff and patients in a social prescribing (SP) pathway and the degree to which these psychosocial processes predict the effect of the pathway on healthcare usage.DesignMixed-methods: Study 1: semistructured interviews; study 2: longitudinal survey.SettingAn English SP pathway delivered between 2017 and 2019.ParticipantsStudy 1: general practitioners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
275
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(287 citation statements)
references
References 46 publications
5
275
0
7
Order By: Relevance
“…Nevertheless, this preliminary research does demonstrate that GPs found it challenging to have good knowledge of community groups or the time to engage fully, but valued face-to-face meetings with them [24]. GPs were also reported to find it difficult to address patient's social and mental health needs, due to lack of training and limited time in appointments; GPs acknowledged the limitations of the "traditional medical model" [25]. And so, this stresses the importance of pursuing this line of inquiry, to understand the role of GPs in social prescribing more clearly.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, this preliminary research does demonstrate that GPs found it challenging to have good knowledge of community groups or the time to engage fully, but valued face-to-face meetings with them [24]. GPs were also reported to find it difficult to address patient's social and mental health needs, due to lack of training and limited time in appointments; GPs acknowledged the limitations of the "traditional medical model" [25]. And so, this stresses the importance of pursuing this line of inquiry, to understand the role of GPs in social prescribing more clearly.…”
Section: Introductionmentioning
confidence: 84%
“…It also appears to rely on GP "buy-in" to validate the service among other professionals and patients, and requires GPs to believe in the link worker's ability and in the benefits of social prescribing [22]. Further, a few studies have included interviews with GPs, but these have tended to involve a very small number of GP interviews, or focused solely on 1 practice or locale [24,25]. Nevertheless, this preliminary research does demonstrate that GPs found it challenging to have good knowledge of community groups or the time to engage fully, but valued face-to-face meetings with them [24].…”
Section: Introductionmentioning
confidence: 99%
“…1 The prescription can take many forms, depending on the community and resources available and patient's needs, but can include a knitting circle, walking group, bereavement support group, or volunteering. Multiple studies indicate that these prescriptions improve social inclusion [2][3][4][5] , mental well-being, 6 physical activity levels, 7 and selfmanagement of health. 8,9 However, beyond identifying the impact of these prescriptions, it is equally important to understand how SP as a process facilitates these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, beyond identifying the impact of these prescriptions, it is equally important to understand how SP as a process facilitates these outcomes. As such, this paper builds on the work done by Hanlon et al, 10 Kellezi et al 3 and Payne et al 11 in trying to understand the "how" of SP.…”
Section: Introductionmentioning
confidence: 99%
“… 35 Our program health coach functioned similarly to the “social prescribing” pathway recently described in England, where primary care providers can refer patients to a health coach for connection to community programming which led to decreased loneliness. 36 The purpose-driven nature of the classes 12 may also represent key element, contrasting with less successful approaches such as “Senior Meetings” 37 where the purpose is explicitly fostering companionship.…”
Section: Discussionmentioning
confidence: 99%